Model of Optimization of Production Based on the Application of Lean Tools to Increase Productivity in Footwear Manufacturing SMEs - Pacora Valverde, Alejandra Lisseth (2023)
The demand for footwear in Peru has increased significantly in recent years even though domestic production has decreased, on the other hand, it has been shown that imports have grown substantially. This shows that the domestic sector has difficulties in offering good quality products, which is directly related to low productivity and lack of innovation. In this sense, an integral Lean-SLP model is proposed based on the combination of tools such as total redesign of facilities, 5s, process standardization, work design, and Jidoka to improve the current productivity of 0.56 generated by deficient and non-standardized processes. The model was validated through arena software where a cycle time reduction of 42.95% and a productivity increase of 22.5% were obtained. This proposal allows SMEs in the footwear sector to be more competitive in the foreign market by producing shoes of higher quality and therefore better acceptance.